An archaeology of the contemporary era - González Ruibal, Alfredo (Routledge, 2019)
"This book approaches the contemporary era--a period comprised between the late nineteenth and the twenty first centuries--as an archaeological age that can be defined by specific material processes. It argues that the materiality of our era, and particularly its ruins and rubbish, tells something profound and original about us--something disturbing, as well. The aim of the book is twofold: it reflects on the theory and practice of the archaeology of the contemporary past--its epistemology, politics, ethics and aesthetics--and it seeks to characterize the present based on the three excesses that define it: spatial, temporal and material. All of them leave traces that can be explored archaeologically. This is the first attempt at describing the contemporary era from an archaeological point of view. Global in scope, the case studies that illustrate the argument come from every continent. The bibliography is also global and includes works from peripheral traditions that are rarely considered. This is a book of archaeology, but one that intends to go beyond academic limits. For that, it engages in a dialogue with philosophy, anthropology, history and geography. The book will be essential reading for students and practitioners of the archaeology of the contemporary past, historical archaeology and archaeological theory. But it will also be of interest to anybody concerned with globalization, modernity and the Anthropocene"--